Pengaruh Konsumsi Keripik Singkong Ebi Terhadap Kadar Glukosa Dan Kualitas Tidur Pada Ibu Hamil Di Puskesmas Tompobulu Kabupaten Maros - Tenri Abeng; Andi Nurlinda; Sudirman (Journal of Muslim Community Health, 2021)
Background: One of the risk factors for the death of pregnant women is the existence of health problems such as gestational diabetes mellitus (DMG). Gestational Diabetes Mellitus is a disorder of glucose tolerance that occurs or is known for the first time during pregnancy. This situation usually occurs at 24 weeks of gestation and some of the patient's blood glucose levels will return to normal after delivery. Nutrients that affect sleep quality are inadequate intake. The aim of the study was to determine the effect of cassava chips consumption on glucose levels and sleep quality in pregnant women. Methods: This study used a quasi-experimental method (Experiment) with a pretest-posttest randomized control trial design with control group. Randomization was carried out in this study which aims to allocate subjects into the treatment group and the control group, thus making the two groups comparable. The number of respondents was 20 people, which were divided between the control group and the intervention group respondents. The sample was determined based on distance considerations, the sample whose residence was close to the researcher's address was used as an intervention and far from the researcher was included as the control group. Results: Giving ebi cassava chips has an effect on reducing glucose levels in pregnant women and giving ebi cassava chips has an effect on the quality of sleep in pregnant women at Tompobulu Public Health Center. Ebi cassava chips are given 25gr / day for 30 days to reduce blood glucose levels and improve sleep quality. Suggestions from this study to pregnant women are that pregnant women consume cassava chips to improve blood glucose levels and sleep quality, and hopefully pay more attention to nutritious food. balanced and in accordance with the needs of pregnant women.